Correction: Manipulation of cell adhesion and dynamics using RGD functionalized polymers. Issue 33 (14th August 2017) - Li, Juyi; Yu, Yingjie; Kim, Myungwoong; Li, Kao; Mikhail, John; Zhang, Linxi; Chang, Chung-Chueh; Gersappe, Dilip; Simon, Marcia; Ober, Christopher; Rafailovich, Miriam
Abstract : Correction for 'Manipulation of cell adhesion and dynamics using RGD functionalized polymers' by Juyi Li et al., J. Mater. Chem. B, 2017, DOI: ; Web:10.1039/c7tb01209h .